Modelo social cognitivo en el desarrollo de habilidades sociales en los niños del sub nivel de preparatoria. - Topa Caseres, Nelly Fabiola (2021)
This research project allowed to carry out an analysis on the cognitive process of the boys and girls of the sub-level of the elementary school of “Quisquis” general basic education school with the purpose of improving the teaching-learning process through the development of the social skills using sessions within the classroom and using the playful activities as a methodological strategy so that through play the student learns to function and is adequately integrated into the social environment where they are and thus can fulfill the learning process in an integral way. For the development of the research, a descriptive methodology was applied and its approach was quali-quantitative because the interview, survey and observation techniques were used as techniques, as well as the questionnaire, question's guide and the observation's sheet for the data collection, the same ones that once applied, obtained an improvement of 19% , in relation to the pre-test and post-test in the part of specific behaviors and in the development of social skills of attachment, empathy, assertiveness and coexistence. In conclusion, it can be determined that the management of social skills in the classroom, if it directly influences in the full development like child as a social entity.